DARI MODERAT KE FUNDAMENTAL: Pergeseran Pemahaman dan Ekspresi Keagamaan Perempuan NU di Ponorogo - Isnatin Ulfah (AL-TAHRIR, 2014)
A statement declaring that fundamentalist ideology has passed into Nahdlatul Ulama/NU is not exaggeration. This is a real fact that is currently under progress. A puritan and textual understanding of Islam is no longer alien to members of NU even in its basic strongholds. A crucial changing religious outlook from moderate to fundamental has impinged many NU leaders and proponents in traditional Islamic boarding schools (pesantren). A massive expansion of fundamentalist movement and ideology has marginalized the established moderate view. This study explores its findings regarding such changing religious ideology. It found that many NU members hold commonalities in terms of their religious views with those of fundamentalist discourses. They reject elements of local custom in Islamic practices, endorse formalization of shari’a law and support Islamic caliphate. The other members informed that they totally agree on formalization of shari’a law. This shows the changes in NU from moderate to fundamentalist that rejects to accommodate local culture in Islamic practice but support the formalization of shari’a law.      Keywords: Islamic fundamentalism, traditionalist-moderate Islam, NU, shifting religious views